Sellaphora gologonica sp. nov. (Bacillariophyta, Sellaphoraceae), a new diatom species from a Mediterranean karst spring (Sardinia, Italy) - Lai, Giuseppina G.; Ector, Luc; Lugliè, Antonella; Sechi, Nicola; Wetzel, Carlos E. (Phytotaxa, 2018)
A new epilithic Sellaphora (Bacillariophyceae) species from a karst spring of Sardinia is described based on light and scanning electron microscopic observations. Sellaphora gologonica sp. nov. shares similarities with small-celled Sellaphora previously described from Europe and particularly with S. atomoides, S. hafnearae and S. seminulum. Sellaphora gologonica seems to be related to S. seminulum based on the striae patterns and valve ultrastructure, as well as the sinuous raphe system. The main differences between S. gologonica and S. seminulum lies in its valve shape (small, elliptic to oval), not presenting capitated nor protracted apices, as in the later taxon. Sellaphora gologonica was discovered in freshwater habitats with slightly alkaline and oligotrophic waters presenting medium hardness and mineralization, at the smaller water emergence of karst spring system Su Gologone (Sardinia).